Waste Battery: Harnessing Bioelectricity from Different Types of Food Waste through Microbial Fuel Cells - Balingit, Grant Sethrey S. (Animo Repository, 2022)
As the world continuously advances and develops, there is also a growth in population, where there is an increasing need for energy demand and the amount of food waste produced. Hence, there is a great need to search for solutions that cater to both problems while still being accessible to underprivileged households. This research studied the potential of fruit, meat, and vegetable food wastes in harnessing bioelectricity utilizing a double-chambered Microbial Fuel Cell or MFC. The researchers adapted the methodology of Sambavi et al. (2021) to prepare the MFC setup. Human urine was collected from a healthy individual to serve as an inoculum. The voltage produced by the MFC setup was measured for 14 days to quantify the bioelectricity produced by the MFC using an analog multimeter. One-way ANOVA test revealed that the three types of MFCs did not show any significant difference in the production of electricity [F(2, 39) = 1.307, p = 0.2822]. This suggests that the type of food waste is not a key factor that affects the bioelectricity production of the MFCs. Moreover, the fruit, meat, and vegetable MFCs reached their peak voltage output at different time periods, specifically on the 5th, 2nd, and 3rd day respectively. This suggests that the type of food waste determines the amount of time for the MFCs to reach their peak voltage output. Further studies are recommended to examine the potential of the three types of MFCs in producing bioelectricity.